Desulfurization Process and Kinetics of Fe/Activated Carbon Removal of H2S at Low Temperature. Issue 28 (24th July 2020) - Zhang, Yaolei; Zhang, Zhihong; Liu, Xuedong; Liu, Lin; Peng, Jian
Abstract: Fe/activated carbon desulfurizer is prepared by precipitation method using activated carbon as carrier to remove H2 S. The desulfurizer before and after desulfurization was characterized by XRD, XPS, SEM and N2 adsorption–desorption. The results show that the active component of desulfurizer is Fe2 O3, which reacts with H2 S to form FeS, elemental sulfur and Fe2 (SO4 )3 . The sulfide block the pores, causing the specific surface area, pore volume and fractal dimension to decrease after desulfurization. The effects of gas flow rate, particle size and temperature on the removal of H2 S were investigated by solid‐bed reactor. Based on the above experimental data, an improved unreacted shrinking core model is used to study the kinetics of Fe/activated carbon desulfurization at low temperature. The improved unreacted shrinking core model is used to analyzing experimental data, in which the activation energies of surface reaction and internal diffusion were determined to be 0.8801 and 3.301 kJ/mol, respectively. Abstract : This paper reveals the process of desulfurizer deactivation from the perspective of kinetics, it is found that the activation energy of internal diffusion is much larger than that of surface chemical reaction. Combined with relevant characterization indicates that it is the main reason for the inactivation of desulfurizer that the pore is blocked by desulfurized products. In summary, how to improve the internal mass transfer and avoid the clogging of sulfide products is the direction of developing of desulfurizers in the future.